Dynamics of SARS-CoV-2 in wastewater in three districts of the Buenos Aires metropolitan region, Argentina, throughout nine months of surveillance: A pilot study - Barrios, Melina Elizabeth (2021)
In the current pandemic of COVID-19, sewage surveillance of SARS-CoV-2 genome has been used to complement viral epidemiology in different countries. The aim of this work was to introduce and evaluate this wastewaterbased tool in the metropolitan region of Buenos Aires, Argentina. As a pilot study, surveillance of SARS-CoV-2 in wastewater from three districts of this area was performed for more than nine months from June 2020 to April 2021. Viruses present in the samples were concentrated using polyethylene glycol precipitation and quantified using RT-qPCR CDC N1 assay. Virus recovery for SARS-CoV-2 and a potential surrogate, bovine coronavirus Mebus strain, that shares the Betacoronavirus genus and structural characteristics with SARS-CoV-2, were evaluated after concentration and detection procedures. Recovery of both viruses did not differ significantly, with a median for SARS-CoV-2 and BCoV of 0.085 (95% CI: 0.021-0.179) and 0.262 (95% CI: 1.18 × 10-5-0.564) respectively. The concentration of SARS-CoV-2 genome in wastewater ranged from 10 -1 to 10 3 cg/ml, depending on the wastewater treatment plant, type of collection site, viral recovery of the concentration method and the epidemiological situation of the outbreaks. Significant correlations were observed between SARS-CoV-2 concentration in wastewater and reported clinical cases, reinforcing the utility of this approach to monitor the epidemiological status of populations.